2020
DOI: 10.1021/acs.iecr.0c04483
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Particle Cluster CPFD Simulation in the Acceleration and Stabilized Sections of a Downflow Circulating Fluidized Bed

Abstract: This study reports a numerical hybrid cluster simulation of a downer reactor unit using CPFD Barracuda VR software. This model includes an experimentally determined particle cluster size distribution to describe the particle cluster morphological changes as well as the cluster acceleration. Gas–solid flows are considered for a fluid catalytic cracking catalyst with an apparent particle density of 1722 kg/m3, flowing in a 5.08 cm-ID column with air at 300 K and with a pressure close to atmospheric. Conditions f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Thus, the CPFD methodology involves a discrete particle method, where the fluid phase is treated as a continuum and the catalyst particles (solids) are modeled using Lagrangian computational groups of particles, also called "clouds" or "computational parcels" [26]. These computational parcels are used to represent a certain number of actual catalyst particles that share the same properties, including uniform size, velocity, density, and temperature.…”
Section: Particle-particle Interaction Equationmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the CPFD methodology involves a discrete particle method, where the fluid phase is treated as a continuum and the catalyst particles (solids) are modeled using Lagrangian computational groups of particles, also called "clouds" or "computational parcels" [26]. These computational parcels are used to represent a certain number of actual catalyst particles that share the same properties, including uniform size, velocity, density, and temperature.…”
Section: Particle-particle Interaction Equationmentioning
confidence: 99%
“…This method has rapidly gained significant attention in recent years. This is the case, considering its capabilities for modeling scaled-up units as well as its ability to assist in the optimization of multiphase gas-solid catalytic reactors [26]. HMs for FCC units have primarily been developed using machine learning (ML) algorithms, combined with FPMs, to create simpler, more flexible, accurate, and interpretable models for industrial-scale units [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The multiphase particle in cell (MP-PIC) method adopts an alternative tracking approach by treating groups of particles’ properties as parcels bridging from the Langrangian coordinates to a Eulerian grid, before recycling it back through stress tensors into individual particles. It was first deployed for fluidized beds in 1993 . Barracuda is a commercial computational particle fluid dynamics software that adopts the MP-PIC approach to solve multiphase flows . The attributes of the MP-PIC approach have recently gained considerable interest in various processes, as it has been validated with experimental data, empirical correlations, and industrial applications. Lu et al employed both the two-fluid model (TFM) and the MP-PIC approach for simulating the carbon dioxide photoreduction in annular CFB by varying the initial catalyst bed height and inlet gas velocity, among other parameters, for envisioning the rise in bed height and size of formed bubbles and determined that the MP-PIC approach surpassed the TFM for the motion of the catalyst within a single cell .…”
Section: Introductionmentioning
confidence: 99%
“…These studies are relevant for the full development of industrial scale fluid bed processes. Furthermore, to be successful, the integration of rigorously derived kinetics with CPFD (Computerized Particle Fluid Dynamic) simulations of large-scale downer units is needed, with the inclusion of particle clusters, as developed by the CREC research team and as reported in Table 1 [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%